ACHIEVING OPTIMAL EMPLOYEE PERFORMANCE THROUGH ENVIRONMENT AND SATISFACTION - Arestia, Nova (Universitas Bina Bangsa, 2024)
As digitalization and shifting demographics change the dynamics of the workplace, organizations face the challenge of adapting to these changes while maintaining high employee performance. In maintaining employee performance, organizations must also pay attention to the work environment and job satisfaction of employees. This study aims to examine the effect of work environment on employee performance through job satisfaction. This research uses associative methods with data collected through questionnaires and relevant literature studies. Using the concept of Partial Least Squares (PLS) through WarpPLS 8.0 software, this study explores the relationship between work environment, job satisfaction, and employee performance. The results showed that work environment has a positive and significant effect on job satisfaction, work environment has a positive but insignificant effect on employee performance, and work environment has a positive and significant effect on employee performance through job satisfaction. It is recommended to organizations, so that they can still pay attention and maintain and remind how important it is to create a supportive work environment to increase job satisfaction and employee performance. Further research is recommended to explore additional factors that affect employee performance and increase the number of respondents